Empowering Banda Aceh's Productive Vocational Educators: A Principal-Driven Approach to Cultivating Industry-Ready Expertise - Roslindawati Roslindawati; Khairuddin Khairuddin; Murniati AR (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2024)
This research aims to reveal the principal's scheme for improving the competence of productive teachers at State Vocational Schools in Banda Aceh City. The research method used in this research is a descriptive method with a qualitative approach. The data collection technique was carried out using triangulation, data analysis was inductive/qualitative, and research results were emphasized more. The findings of this research show that the principal's program to improve teacher professional competence includes in-house training, educational seminars, workshops, and the use of IT tools for learning. . Additionally, the principal's strategy involves facilitating educational training and seminars to encourage effective lesson plans and provide guidance to less competent teachers. in terms of supporting factors for increasing professional competence, including discipline, appreciation, and infrastructure. Thus, the results of this research can provide a complete and well-organized picture of certain components so that they can provide valid final results.